'Too-big-to-fail' financial institutions: risks and remedies. (1st January 2011) - Panzera, Fabio; Rossi, Sergio
Too-big-to-fail (TBTF) institutions pose a systemic threat to financial stability, as they exploit the implicit guarantee offered by the State to further increase their businesses as well as the risks they raise for taxpayers. Although TBTF problems have been widely debated in the literature, practical solutions are still lacking in all advanced economies around the world. This paper puts forward a structural reform of banks' bookkeeping, with the aim of refining the latter in order to make it fully transparent, to gain the competitive advantage that results from a financial industry that is more resilient to systemic risks and crises.